PENERAPAN MODEL ACTIVE LEARNING BERBASIS KOOPERATIF UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN KINERJA SISWA (UPEJ Unnes Physics Education Journal, 2013)
Implementation of active learning based cooperative model can improve conceptual undersanding and student's performance. Samples taken as random sampling and obtained VIIIE as experiment-class and VIIIB as control-class. Experiment-class got active learning based cooperative and control-class got active learning discussion. improved conceptual understanding was measured with pretest-posttest and improvement of student's performance was measured with observation. Improved conceptual understanding and the student's performance can be seen through the gain test. The data show that: 1.gain number of conceptual understanding experiment-class was 0,58 (medium) and gain number of conceptual understanding control-class was 0,51(medium)., 2. Gain number of student's performance experiment-class was 0,22 (low) and gain number of student's performance control-class was 0,04 (low). From these results it can be concluded that the application of active learning based cooperative models can improve understanding of concepts and students's performance